Promoting Mathematics Students’ Learning Outcome Using Jarimatika Method For Primary School - Firmansyah, Dani; Syahrilfuddin, Syahrilfuddin; Antosa, Zariul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This study aims to implementation jarimatika method to promote students’ mathematics learning outcome for elementary school. This study was conducted in class third elementary schools. Design of this research was classroom action research. Based on the results of mathematics learning students obtained data on the initial score taken from the scores of the first semester Mathematics exam students before the application of the Jarimatikaini method was 59.62 then the cycle I daily test increased by 13.63 to 73.42 with an increase percentage of 22.80%. It can be concluded that the application of the Jarimatika method can improve the results of third grade elementary school mathematics learning.